Forest demographic changes across Texas associated with hot drought - Shakirudeen Lawal; Frank H. Koch; Robert M. Scheller; Jennifer Costanza (Ecological Indicators)
Recent changes of tree species demography in Texas likely can be attributed to climatic disturbances, particularly hot drought (i.e., drought exacerbated by extreme heat). In this study, we examined demographic change over East, Central and West Texas over a 16-year period (2004–2019), including a widely documented 2011 hot drought event. We used Forest Inventory and Analysis (FIA) data to evaluate changes in tree count for the nine most abundant tree genera in Texas. Furthermore, we examined the associations between tree demography and the distribution of climate variables including the 12-month Standardized Precipitation Evapotranspiration Index (SPEI12), potential evapotranspiration (PET), precipitation, vapour pressure deficit (VPD), maximum temperature and the Heat Wave Magnitude Index daily (HWMId). Using Pearson Correlation Coefficient, we examined the influence of hot drought on forest demography by examining four size classes (seedlings, saplings, small trees and large trees). We found that there were declining trends for most genera between 2004 and 2019, particularly in the seedling and sapling size classes. In East Texas, there were significant decreasing trends of Quercus spp. seedling counts and sapling counts. We also observed significantly declining seedling and sapling counts of Liquidambar and the sapling count of Ulmus. Decreasing counts were most prominent in Central Texas and West Texas, though the patterns and trends were variable among genera. In West Texas, there were declines through time in all but the largest size class for Juniperus and Prosopis. Furthermore, we found that hot drought was correlated with declines in seedling and sapling counts. We demonstrate opportunities for monitoring demographic change, which can be a baseline for improved ecosystem management.